Activated carbon derived from non-metallic printed circuit board waste for supercapacitor application. (1st September 2016) - Rajagopal, Raghu Raman; Aravinda, L.S.; Rajarao, Ravindra; Bhat, Badekai Ramachandra; Sahajwalla, Veena
Abstract: Activated carbons (ACs) have been synthesized by using waste PCBs via physical activation subsequent to pyrolysis processes. The physical and chemical properties of the produced activated carbons were studied using nitrogen adsorption, FT-IR spectroscopy, RAMAN spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and scanning electron microscopy techniques. Among the synthesized ACs, AC with the highest surface area of 700 m 2 g −1 produced at 850 °C for a time interval of 5 h was subjected to electrochemical studies. Capacitance behaviour of the obtained AC sample has been evaluated using cyclic voltammetry (CV), galvanostatic charge–discharge (GC-D) measurements and electrochemical impedance spectroscopy (EIS) technique. Specific capacitance (Cspec ) values vary from 220, 185 and 156 F g −1 for corresponding scan rate of 30, 50 and 100 mV s −1 respectively. The well-developed surface area properties and good capacitance values associated with nitrogen functionalities indicates the AC developed is a good and suitable candidate for the supercapacitor fabrication.